2015
DOI: 10.1080/17458080.2015.1012654
|View full text |Cite
|
Sign up to set email alerts
|

Metastableh-MoO3and stableα-MoO3microstructures: controllable synthesis, growth mechanism and their enhanced photocatalytic activity

Abstract: Metastable h-MoO 3 hexagonal prisms have been fabricated through a simple green ultrasonic-assisted chemical route. After calcination at 440 C for 2 h, the thermodynamically stable a-MoO 3 nanoplate-based rods have been achieved through a process of in situ phase transformation. The as-synthesised products have been characterised by powder X-ray diffraction, field emission scanning electron microscopy, Fourier transform infrared spectrum, UVÀvis diffuse reflection spectroscopy and photoluminescence spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(51 citation statements)
references
References 31 publications
4
44
1
2
Order By: Relevance
“…05‐0508), indicating the poor crystallinity. Meanwhile, for the ultrasonicated sample, it is noteworthy that the diffraction peaks at 19.4° and 25.7°correspond to (200) plane of h‐MoO 3 and (040) plane of α‐MoO 3 , respectively, suggesting that MoO 3 layers have a certain extent crystal structure . XRD analysis are consistent with HRTEM images of both samples.…”
Section: Figuresupporting
confidence: 73%
“…05‐0508), indicating the poor crystallinity. Meanwhile, for the ultrasonicated sample, it is noteworthy that the diffraction peaks at 19.4° and 25.7°correspond to (200) plane of h‐MoO 3 and (040) plane of α‐MoO 3 , respectively, suggesting that MoO 3 layers have a certain extent crystal structure . XRD analysis are consistent with HRTEM images of both samples.…”
Section: Figuresupporting
confidence: 73%
“…The X‐ray diffraction (XRD) patterns and Raman spectra of the powder samples shown in Figure a confirm the obtainment of hexagonal molybdenum oxide with a certain extent of amorphization. Three characteristic vibrational modes of both samples at shifts of 690, 900, and 978 cm −1 are observed in the Raman spectrum (Figure b), all of which are in good agreement with hexagonal h‐MoO 3 . Broad Raman bands of amorphous molybdenum oxide can be found at shifts of approximately 860 and 950 cm −1 .…”
Section: Figuresupporting
confidence: 66%
“…It can be observed that the pure H x MoO 3− x sample is mostly formed from nanorods with amorphous edges. Usually, hexagonal molybdenum oxide is a metastable phase, which is favorable for its transformation into 2D molybdenum oxide . Besides, the amorphous structure is known to possess high HER activity, primarily as a result of more active sites .…”
Section: Figurementioning
confidence: 99%
“…The photodestruction of RhB is not observed in the absence of the catalyst. It should be noted that the rate of dye destruction in the presence of the obtained composite is higher than that observed in Reference [67], where 100% degradation was achieved in 180 min for α-MoO 3 nanostructures. At the same time, the obtained rate of destruction of the dye is comparable with the values obtained in Reference [68], where the powder containing MoO 2 nanoparticles was used.…”
Section: Photocatalytic Activity and Photodestruction Of Rhbcontrasting
confidence: 59%